Graph Representation for the Solutions of Pythagorean Equation over the General Linear Group GL₂ (ℤ₂ ) - Mahatma, Yudi; Hadi, Ibnu; Sudarwanto, Sudarwanto; Agustine, Debby (JMT (Jurnal Matematika dan Terapan), 2025)
In 2023, Hadi et al. found the solvability of the Fermat equation over the general linear group GL2(Zp) for p=2 and p=3. In particular, for Pythagorean equation over GL2(Z2) there are 12 solutions. In this research, we represent the set solutions as a graph and investigate the properties.